Pesantren as the Source of Peace Education - Francoise, Jeanne (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
This paper gives a new perspective about pesantren (Islamic boarding school) as the source of peace education in Indonesia using three concepts; First is a collective opinion that reflected in the UN Declaration of Culture of Peace, second is the definition of peace education based on peace and conflict resolution studies, and third is the historical side of Islam in Indonesia. To explain the main idea about pesantren as the source of peace education, this paper uses the qualitative method in analyzing the data from interviews in some pesantren in Madura Island in 2014. This paper constructs a hypothesis that pesantren is the unique source and very potential for creating Indonesian peace leaders in the future. This idea is simply coming from a common sense that Muslims majority in Indonesia send their children to the pesantren to have a good education and good manner as well. But on the other side, some pesantren precisely create some radicals, so I would like to uphold this issue by telling the Union European historical experience to handle radicalizes through peace education by harmonizing state-religion relationship.Makalah ini memberikan perspektif baru tentang pesantren sebagai sumber pendidikan perdamaian di Indonesia dengan menggunakan tiga konsep; Pertama adalah pendapat kolektif yang tercermin dalam Deklarasi Budaya Damai PBB, kedua adalah definisi pendidikan perdamaian berdasarkan studi resolusi perdamaian dan konflik, dan ketiga adalah sisi historis Islam di Indonesia. Untuk menjelaskan tentang ide utama pesantren sebagai sumber pendidikan perdamaian, makalah ini menggunakan metode penelitian kualitatif dengan menganalisis hasil wawancara di beberapa pesantren di Pulau Madura pada tahun 2014. Makalah ini membangun sebuah hipotesis bahwa pesantren adalah sumber unik dan sangat potensial menciptakan pemimpin perdamaian Indonesia di masa depan. Gagasan ini muncul dari fenomena kecenderungan mayoritas Muslim Indonesia, yang mengirim anak-anak mereka ke pesantren agar mendapatkan pendidikan dan perilaku yang baik. Namun di sisi lain beberapa pesantren justru menciptakan radikalis. Oleh karenanya penulis ingin mengemukakan masalah ini dengan berkaca pada pengalaman sejarah Uni Eropa dalam menangani para radikalis melalui pendidikan perdamaian dan menyelaraskan hubungan antara Agama dan Negara.